Enhanced adhesion of blood platelets to intact endothelium of mesenteric vascular bed in mice with streptozotocin-induced diabetes is mediated by an up-regulated endothelial surface deposition of VWF – In vivo study. (4th July 2018) - Przygodzki, Tomasz; Talar, Marcin; Kassassir, Hassan; Mateuszuk, Lukasz; Musial, Jacek; Watala, Cezary
Abstract: Numerous in vitro experiments have confirmed that a dysfunctional endothelium is characterized by, inter alia, a higher affinity for binding of platelets and leukocytes. However, there is still no direct evidence for greater interaction between platelets and intact endothelium in in vivo animal models of diabetes. Therefore, the present study examines the pro-adhesive properties of endothelium change in vivo as an effect of streptozotocin (STZ)-induced diabetes and the role of two key platelet receptors: GPIb-IX-V and GPIIb/IIIa. Mice of C57BL strain with streptozotocin-induced diabetes were used in the study. Flow cytometry was used to assess basal activation and reactivity of platelets. Adhesion of platelets to the vascular wall was visualized with the use of intravital microscopy in mesentery. The contribution of GPIIb/IIIa and GPIb-IX-V was evaluated by the injection of Fab fragments of respective antibodies. The integrity of the endothelium and vWf expression were evaluated histochemically. Basal activation and reactivity of platelets in streptozotocin-diabetic mice were elevated. Blood platelets adhered more often to the vascular wall of diabetic mice than nondiabetic animals: 11.9 (6.4; 32.8) plt/min/mm 2 (median [IQR]) vs 2.7 (1.3; 6.4) plt/min/mm 2 . The injection of anti-GPIbα antibodies decreased the number of adhering platelets from 89.5 (34.0; 113.1) plt/min/mm 2 (median [IQR]) in mice treated with isotype antibodies to 3.1 (1.7; 5.6) plt/min/mm 2 in mice treated with blocking antibodies. The effect of GPIIb/IIIa blockage was not significant. Immunohistochemistry revealed a higher expression of vWF in the endothelium of STZ mice, but no substantial changes in endothelial morphology were detected. To conclude, the study shows that the platelets interact more frequently with the mesenteric vascular bed in mice with 1-month STZ-induced diabetes than in healthy mice. These interactions are mediated via platelet GPIb-IX-V and are driven by increased expression of vWF in endothelial cells.